INVESTMENT ANALYSIS OF YANDEX: A CASE OF STUDY FOR 2022-2024 - Veronika Demenchuk; Inaya Sari Melati Melati; Diana Utesheva (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study analyzes the investment attractiveness of Yandex, Russia’s leading technology company, during 2022–2024, focusing on its performance amid a dynamic and volatile global economic environment. Methods: The research employs a mixed-methods approach, integrating quantitative analysis of financial indicators such as revenue growth, adjusted EBITDA, and net income, with qualitative evaluation of Yandex’s strategic business segments. Data were collected from official company reports and reputable international sources. Results: Findings reveal that Yandex achieved record revenues in 2024, driven by innovations in advertising technology and expansion of its digital ecosystem. Despite challenges including segment losses and dependence on the Russian domestic market, the company’s diversification, strong market share, and continuous innovation have enhanced its resilience and long-term growth prospects. Conclusion: The study concludes that Yandex is well-positioned for sustained value creation, leveraging strategic initiatives in artificial intelligence and international expansion to maintain competitive advantage in an uncertain geopolitical climate. These insights offer valuable guidance for investors and stakeholders interested in high-tech firms operating in complex environments Keyword: Investment analysis; Yandex; Financial performance; Digital transformation; International sources;